English for tourism 3 (Can Tho University, 2020)
The text book consists of 3 parts which focus on 3 tourism sectors: guiding, catering and accomodation. Each unit consists of are three sections. Section 1 focuses on language materials used in tourism situtations while section 2 aims at giving students different reading skills, section 3 is the final step to help students review what they have learned.